Properties of eggshell powder filled low density Polyethylene/ Acrylonitrile Butadiene Styrene Composites - Mohammed Jasim Mohammed Al-Jumaili (School of Materials Engineering, 2009)
The objectives of this study are to study the effect of modified eggshell powder on mechanical and tensile fracture surface properties of LDPE/ABS composite; to study water absorption of LDPE/ABS composite with and without modification by using swelling behavior test; to study the effect of modified eggshell powder on thermal properties and thermal degradation of LDPE/ABS composite by using differential scanning calormetry (DSC) and thermogravimetry analysis (TGA); and to analyze the d-spacing of eggshell powder filled LDPE/ABS composite by using X-ray diffraction (XRD).